The antitumor activity of CYB-L10, a human topoisomerase IB catalytic inhibitor. (1st January 2019) - Yu, Qian; Chen, Yu; Yang, Hui; Zhang, Hong-Li; Agama, Keli; Pommier, Yves; An, Lin-Kun
Abstract: DNA topoisomerase IB (TOP1) is a validated target for discovery and development of antitumor agents. Four TOP1 poisons are clinically used for tumor treatment now. In spite of their effectiveness in solid tumors, these camptothecin (CPT) poisons suffer from many shortcomings. Therefore, many investigations have focused on the discoveries of non-CPT poisons and catalytic inhibitors. Herein, we systematically study the antitumor activity of CYB-L10, a novel indolizinoquinolinedione TOP1 catalytic inhibitor discovered in our laboratory. The results indicated that CYB-L10 mainly acts on TOP1 in cancer cells and is not a substrate of the P-glycoprotein. In addition, CYB-L10 can induce apoptosis of HCT116 cells, shows high cytotoxicity against 60 human clinical cancer cell lines (NCI60) with the mean-graph midpoint for growth inhibition of all cancer cell lines of 0.050 µM concentration and obvious antitumor efficiency in vivo in the HCT116 xenograft model.